Eliminating perinatal HIV in the United States: mission possible?. (1st March 2019) - Gnanashanmugam, Devasena; Rakhmanina, Natella; Crawford, Keith W.; Nesheim, Steven; Ruel, Theodore; Birkhead, Guthrie S.; Chakraborty, Rana; Lawrence, Robert; Jean-Philippe, Patrick; Jayashankar, Lakshmi; Hoover, Ashley; Statton, Anne; et al.
Abstract : N/A: In 2015, only 53 infants born in the United States acquired HIV – the lowest recorded number of perinatal HIV infections. Recognizing this significant achievement, we must acknowledge that the United States has not yet reached the goal of eliminating perinatal HIV transmission. This analysis describes different approaches to perinatal HIV preventive services among five states and the District of Columbia as case studies. Continuous focus on improving identification, surveillance and prevention of HIV infection in pregnant women and their infants is necessary to reach the goal of eliminating perinatal HIV transmission in the United States.